2016
DOI: 10.1038/srep31593
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of liraglutide using thermogelling polymers in treatment of diabetes

Abstract: In treatment of diabetes, it is much desired in clinics and challenging in pharmaceutics and material science to set up a long-acting drug delivery system. This study was aimed at constructing a new delivery system using thermogelling PEG/polyester copolymers. Liraglutide, a fatty acid-modified antidiabetic polypeptide, was selected as the model drug. The thermogelling polymers were presented by poly(ε-caprolactone-co-glycolic acid)-poly(ethylene glycol)-poly(ε-caprolactone-co-glycolic acid) (PCGA-PEG-PCGA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 65 publications
1
61
0
Order By: Relevance
“…Previous reports have indicated that GPC often yields higher values than those determined by 1 H‐NMR, and this effect has been observed by other researchers for PEG‐PLGA polymers. For example, it was reported that M n by GPC was 31% higher than that obtained by 1 H‐NMR for PLGA‐PEG‐PLGA . The GPC‐ES results relative to the NMR data in this study varied across the polymers.…”
Section: Discussionmentioning
confidence: 50%
“…Previous reports have indicated that GPC often yields higher values than those determined by 1 H‐NMR, and this effect has been observed by other researchers for PEG‐PLGA polymers. For example, it was reported that M n by GPC was 31% higher than that obtained by 1 H‐NMR for PLGA‐PEG‐PLGA . The GPC‐ES results relative to the NMR data in this study varied across the polymers.…”
Section: Discussionmentioning
confidence: 50%
“…As examples of using peptide/protein drugs, a delivery system for liraglutide (Lira), a fatty acid- As for the drugs for drug delivery systems, peptide/protein drugs and genes should be considered because their use as therapeutic agents has increased considerably in recent years. As examples of using peptide/protein drugs, a delivery system for liraglutide (Lira), a fatty acid-modified antidiabetic polypeptide, for the treatment of diabetes was investigated by Chen et al [44], and controlled release of growth hormone-releasing peptide 6 (GHRP-6) for the growth of rex rabbits was investigated by Guan et al [45]. In order to prolong the bioactivity of peptide/protein drugs, an incorporation into microparticles and a complex formation were performed.…”
Section: Applications Of Thermoresponsive Hydrogels Using Block Copolmentioning
confidence: 99%
“…Chen et al developed a sustainable Liraglutide (drug for Type 2 diabetes) release system consisting of poly(ε‐caprolactone‐co‐glycolic acid)‐poly(ethylene glycol)‐poly(ε‐caprolactone‐co‐glycolic acid) (PCGA–PEG–PCGA) thermogels. They reported a sustained release for 1 week in mice, attributed to the amphiphilicity of Liraglutide and the high chain mobility of the PCGA part at body temperature . The delayed diffusion of drug was due to hydrophobic interactions between C16 fatty side chain of Lira and the hydrophobic cores of copolymer micelles.…”
Section: Thermogelling Mechanismmentioning
confidence: 99%